STUDI TENTANG DISAIN RAGAM HIAS PAKAIAN PENGANTIN TRADISIONAL LUBUK BEGALUNG PADANG - Desmaleni, Rahayu; Efi, Agusti; Yuliarma, Yuliarma (Journal of Home Economics and Tourism, 2014)
The problem in this study is about decorative design of traditional bridal costumein Lubuk Begalung Padang which is undergoing changes. It happens because of the traditional bridal costume is now used as a fashion service industry, so that many people in Padang, especially the younger generation do not know the bridal costume ranging from traditional bridal costume of brideuntil traditional bridal costume ofbridegroom. This study aims to describe the decorative design of a traditional bridal costumein Padang. The method that used in this study is a qualitative case study method . The type of data is primary that are data from management and employees of businesses and secondary data obtained from the documentation. The technique of collecting data through observation, interview and documentation. The analysis technique is inductive based on the facts that already found and it can be constructedthen into a hypothesis or theory . In order to obtain the valid data, the researchers tested the validity of the data by means of an extension of the observation, diligence research, triangulation and auditing . The results of the study are: the decorative design of a traditional bridal costumein Lubuk Begalung Padang,for the bridal costume ofbridegroom is baju rokiusing a star, a butterfly and a tabua roti motif with taburan loyanglatching, on celana roki and waistcoatusing lace gold thread latching. Motives are used by sisamping: itik pulang patang, bada Mudiak, batang pinang, bungo sikakau, salapah, balah kacang, pucuk rabuang, and salauak laka.Sisamping derived from pandai sikekwoven red base color . The bridal costume ofbride isBaju kurung,known as "baju kurung bajaik". It is using florals located on the front/chest and the surface of baju kurung, phoenix on the surface using gold thread embroidery and suji kapalo samek, decorative patterns found on the baju kurungaresowing pattern, the fringe standspattern, dependent peripherypattern, the periphery runspattern, and decorative patterns fill the triangular fields.Kodekorsarong is red base color of songket came frompandai sikek woven using itik pulang patangmotif, bada mudiakmotif, batang pinangmotif, bungo cukia kaluakmotif, salapahmotif, balah kacangmotif, pucuk rabuangmotif, and salauak lakamotif. Kata Kunci: Pakaianpengantin tradisional, disain ragam hias, motif, kombinasi warna, teknik hias, pola hias Lubuk Begalung Padang